(untitled) (Asian Journal of Medical and Biological Research, 2020)
The study was conducted at Upazila Livestock Office, Sadar, Dinajpur of Bangladesh from January 2018 to December 2018 to investigate the incidence of reproductive disorders in goat. Data on reproductive disorders were collected on the basis of owner’s complain and observed clinical signs. Age and season wise occurrences of reproductive disorders were also recorded. Descriptive statistical analysis was done. Out of 2484 clinical cases, a total of 107 reproductive disorders of goat were recorded. Incidence of abortion (38.3%) was higher and pyometra (0.9%) was lower among reproductive disorder in goat. The incidence of reproductive disorders of goat was higher in group-2 (above 1-2 years) (36.4%) followed by group-1 (upto 1 year) (21.6%), group-3 (above 23 years) (21.5%), group-5 (above 4 years) (15.3%) and group-4 (above 3-4 years) (3.6%). Among reproductive disorders, the incidence of abortion was higher in group-2 (58.9%) followed by retained placenta (50%) in group-4, metritis (47%) and dystocia (23.5%) in group-5, repeat breeding (17.4%) and anestrus (4.3%) in group-3, and pyometra (2.5%) in group-2. Slight seasonal variation among individual case of reproductive disorders were recorded, highest in winter (34.5%) than summer (32.4%) and rainy season (31.7%). The incidence rate of abortion was high in each season (summer 25%, rainy 32.3% and winter 56.7%). In case of retained placenta and dystocia, the incidence was high in summer season (22.2%). But in case of metritis and repeat breeding, the incidence was high in rainy season (32.3% and 14.7% respectively). For treatment of reproductive disorders in goat, antibiotics drugs (35%) were used most commonly and hormonal drugs (3%) used in lower percentages. It was concluded that the most pressing constraint on goat reproduction in Bangladesh is abortion, retained placenta, dystocia and metritis. Strategies should be taken to minimize their occurrence. Asian J. Med. Biol. Res. June 2020, 6(2): 212-221